Applications of the 3-min all-out exercise test for prescribing high-intensity interval training: A narrative review on a decade of research progress - Pettitt, R. W.; Dicks, N. D.; Kramer, M. (Strength and Conditioning Journal, 2025)
The 3-minute all-out exercise test (3MT) was developed over a decade ago and enables the estimation of time for onset of momentary fatigue for a given speed or power output exceeding critical speed (CS) or critical power (CP), respectively. The 3MT has been validated for conducting high-intensity interval training, used with load carriage prediction and prescription, and validated for shuttle running. These prescriptions are novel because they allow for standardizing exercise intensities relative to metabolic parameters as opposed to a percentage of a given maximum or reserve. Research was identified using leading search engines (e.g., PubMed, Google Scholar, and Research Gate) and citations to similar articles. The objective of this review article was to summarize research that emerged on the CS/CP concept with emphasis on applications since the advent of the 3MT. The review concludes with application of the CS/CP concept to the frequency, intensity, time, and type of exercise for exercise prescription.